Estudo da metilação nos genes IFN-y e IL-10 na doença periodontal - Michelle Beatriz Viana (2009)
DNA methylation is characterized by the addition of methyl groups in cytosines within CpG islands. Unmethylated CpGs are related with transcriptionally active structure, whereas methylated CpG recruits methyl-binding proteins that promotes chromatin compaction. DNA methylation can influence the expression of cytokines and to affect the development of periodontal disease. The purpose of the present study was to evaluate the methylation status of the interferon gamma (IFN-g) and interleukin-10 (IL-10) gene in periodontal tissues. Methylation-specific polymerase chain reaction (MSP) and DNA sequencing analysis were used to verify the DNA methylation status of the IFN-g and IL-10 gene, respectively, in samples from no periodontitis subjects and individuals with chronic periodontitis. Histologic sections stained by hematoxylin-eosin were used for histopathological evaluation of samples. The methylation status of the IFN-g and IL-10 gene were similar among the groups. Most of samples were positive for IFN-g methylation. Only 11% of periodontitis group showed unmethylated DNA. Considering IL-10 gene, no unmethylated sample was observed. The profile of total or partial methylation were detected in CpGs evaluated. The results showed evidence that methylation of IFN-g and IL-10 genes are usual features on periodontal tissues. Further studies are necessary to determine the functional relevance of these alterations.